Bio-inspired catalyst compositions for enhanced oxygen reduction using nanostructured Pt electrocatalysts in polymer electrolyte fuel cells - Parthasarathy, Meera; Kannan, Ramaiyan; Sreekumar, Kurungot; Pillai, Vijayamohanan K. (Journal of Materials Chemistry, 2010)
Composites of Nafion with a class of bio-molecules viz., plant hormones, are explored as potential polymer electrolytes for improving the proton transport inside the catalyst layer of a H(2)/O(2) fuel cell. Specifically, four nitrogenous plant hormones, two each from the class of auxins and cytokinins have been investigated, following preliminary characterization of the composite dispersions and membranes. Interestingly, the use of indole-3-acetic acid (an auxin) in the catalyst layer reveals a 30% enhancement in Pt catalyst utilization and improved fuel cell performance by 150 mW cm(-2). The effect of these bio-molecules on the kinetic and mass transport parameters has been analyzed systematically using a combination of electrochemical and spectroscopic techniques.

Disordered brownmillerite Ba2InCeO5+delta with enhanced oxygen reduction activity - Jijil, Chamundi P.; Unni, SreeKuttan M.; Sreekumar, Kurungot; Devi, R. Nandini (Chemistry of Materials, 2012)
A disordered brownmillerite, Ba2InCeO5+delta, with slight tetragonal distortion from ideal cubic perovskite is synthesized and its oxygen reduction reactivity tested. The material displayed oxygen reduction behavior in alkaline solution comparable to that of standard 40 wt % Pt/C catalyst and attractive activity characteristics which renders it a potential system for low temperature fuel cell applications.
Keywords: brownmillerite; fuel cell; oxygen reduction reaction; Rietveld refinement

Layered TiO2 nanosheet‐supported NiCo2O4 nanoparticles as bifunctional electrocatalyst for overall water splitting - Raji, Vadakkekara; Rajith, Illathvalappil; Sreekumar, Kurungot (ChemElectroChem, 2018)
Exploring the generation of efficient and long‐lasting bifunctional electrocatalysts obtained from low‐cost transition metal oxides is crucial to the optimal production of hydrogen and oxygen by electrocatalytic water splitting. This study aims to demonstrate the applicability of layered TiO2 nanosheets as support for designing electrocatalysts. We have demonstrated the performance by decorating the TiO2 support with NiCo2O4 nanoparticles (NiCo2O4/TiO2) as catalysts for electrocatalytic overall water splitting. Moreover, the corrosion effect of usually used carbon‐based supporting materials can decrease the working efficiency and, thus, the overall performance of the catalysts. In this aspect, TiO2 can be a better alternative to carbon‐based systems. Layered TiO2 was synthesized at room temperature, and a simple heat treatment protocol was employed for the large‐scale synthesis of NiCo2O4/TiO2. TiO2 facilitated the formation of smaller NiCo2O4 nanoparticles, also improving the dispersion. This bifunctional electrocatalyst exhibits high OER and HER performance with a low overpotential of 309 mV and 185 mV respectively, at a current density of 10 mA cm−2. TiO2 supported catalyst also exhibits other advantages like remarkable durability in the alkaline medium along with high turnover frequency (TOF) values. This inexpensive catalyst can deliver a current density of 10 mA cm−2 at only 1.64 V with a steady performance for more than 12 h for overall water splitting. Thus, this homemade system provides a proficient and low‐cost alternative to the more expensive systems such as RuO2, IrO2 or Pt for the electrochemical water splitting applications.

Medium modulated oxygen reduction activity of Fe/Co active centre-engrafted electrocatalysts - Kashyap, Varchaswal; Anand, Aljo; Soni, Roby; Sreekumar, Kurungot (ChemElectroChem, 2019)
Iron and cobalt metal atoms are effective active centers for the synthesis of carbon-based noble-metal-free catalysts for the oxygen reduction reaction (ORR) owing to their cost-effective intrinsic activity and tunable properties. Annealing of the active center with the conducting carbon enhances the ORR activity significantly. Herein, we have engrafted Fe and Co active centers in the homemade conducting carbon and the ORR performance has been closely observed under acidic and basic pH conditions to understand the influence of the medium and participating moieties towards the performance. In the half-cell reaction, the onset potential and half-wave potential for ORR are governed by the surface intermediates and concomitantly driven by the adsorption energies of the intermediates over the active centers. The iron and cobalt active center-engrafted carbon catalyst behaves differently in acidic and basic electrolytes owing to the dissociation of the surface intermediates. The iron-based catalyst shows improved onset potential against the cobalt-based one. Similarly, the cobalt-based catalyst shows improved half-wave potential against the iron active-center-grafted catalyst. The combined synergistic effect of the two catalysts is realized in the composition represented as Fe/2Co-N-GVC, where improved onset and half-wave potentials are noted in basic medium. A significant variation in the activity of the catalyst is observed as the medium changes from acidic to basic and the effect is directly associated with the surface adsorption of the intermediates.
Keywords: active centers; half-wave potential; Mechanism; oxygen reduction reaction; transition state